2001
DOI: 10.1038/sj.onc.1204106
|View full text |Cite
|
Sign up to set email alerts
|

Muc4/sialomucin complex, an intramembrane modulator of ErbB2/HER2/Neu, potentiates primary tumor growth and suppresses apoptosis in a xenotransplanted tumor

Abstract: Overexpression of the membrane mucin MUC4/Sialomucin complex (SMC) has been observed during malignant progression of mammary tumors in both humans and rats, suggesting that deregulation of MUC4/SMC expression might facilitate development of these malignancies. As previously reported, overexpression of SMC results in suppression of both cell adhesion and immune killing of tumor cells. SMC also acts as a ligand for ErbB2/Neu, modulating phosphorylation of the receptor tyrosine kinase in the presence and absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 36 publications
6
94
0
Order By: Relevance
“…In our previous studies, inhibition of MUC4 expression reduced in vitro growth of pancreatic cancer cells (Singh et al, 2004). Another study performed on rat Muc4/SMC also proves the involvement of MUC4 mucin in growth advantage to cancer cells (Komatsu et al, 2001). In this study, the ectopic expression of mini-MUC4 showed an increased in vitro growth.…”
Section: Discussionsupporting
confidence: 72%
“…In our previous studies, inhibition of MUC4 expression reduced in vitro growth of pancreatic cancer cells (Singh et al, 2004). Another study performed on rat Muc4/SMC also proves the involvement of MUC4 mucin in growth advantage to cancer cells (Komatsu et al, 2001). In this study, the ectopic expression of mini-MUC4 showed an increased in vitro growth.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, mucin-type glycoproteins, such as podoplanin, are expressed widely on human normal cells and tumors [26][27][28] and have recently been implicated in cellular signaling, cell adhesion, tumor growth, and suppression of apoptosis. [29][30][31][32][33] We have recently characterized the immunohistochemical reactivity of tumor cells in a series of earlystage cervical squamous cell carcinomas with the D2-40 antibody and found that low levels of podoplanin expression in the tumor cells were significantly associated with the presence of lymphatic invasion and lymph node metastasis, as well as with shorter survival and higher risk of tumor recurrence. 16 Interestingly, we found that tumor emboli within lymphatic spaces, as well as metastatic tumor cells in lymph nodes, showed no podoplanin immunostaining in the vast majority of tumors, even in cases when the main tumor mass was D2-40 positive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the emerging importance of the MUC4 mucin in tumour biology (Komatsu et al, 1999(Komatsu et al, , 2001Singh et al, 2004), the molecular mechanism(s) that lead to its deregulated expression in tumour cells is largely unknown. The expression of MUC4 is developmentally regulated and varies with the degree of tissue differentiation (Buisine et al, 1998(Buisine et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…SMC/Muc4 acts as a ligand for ErbB2/HER2 inducing its limited phosphorylation (Jepson et al, 2002). The overexpression of SMC results in the suppression of both cell adhesion and immune killing of tumour cells, enhanced tumour growth and potentiation of metastasis (Komatsu et al, 1999(Komatsu et al, , 2000(Komatsu et al, , 2001. However, despite all these pathobiological implications of MUC4 in tumour biology, suggesting its importance as a potential therapeutic target, the molecular mechanisms implicated in its regulation have remained ill-defined.…”
Section: Introductionmentioning
confidence: 99%